Late Victorian orientalism : representations of the East in nineteenth-century literature, art and culture from the Pre-Raphaelites to John La Farge /: representations of the East in nineteenth-century literature, art and culture from the Pre-Raphaelites to John La Farge. (2020) - Unknown
No abstract available